2017
DOI: 10.1016/j.carpath.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms in the pathogenesis of arrhythmogenic cardiomyopathy

Abstract: The article is based on work presented in the Distinguished Achievement Award lecture at the Society for Cardiovascular Pathology meeting in Seattle, WA in March, 2016. It reviews our current understanding of mechanisms responsible for a highly arrhythmogenic, non-ischemic cardiomyopathy. It highlights the armamentarium of powerful methods available to the experimental pathologist in efforts to define how complex cardiovascular diseases work. It concludes with acknowledgment of the need for a far more detailed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…NF k B activation has been previously linked to the development of renal diseases [ 72 ]. Wang et al [ 73 ] found that nephropathy is mediated via activation of the tumor necrosis factor/NF k B pathway As NF k B regulates inflammatory factor transcription in mesangial and tubular epithelial cells, it plays a vital role in the development and progression of renal diseases [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…NF k B activation has been previously linked to the development of renal diseases [ 72 ]. Wang et al [ 73 ] found that nephropathy is mediated via activation of the tumor necrosis factor/NF k B pathway As NF k B regulates inflammatory factor transcription in mesangial and tubular epithelial cells, it plays a vital role in the development and progression of renal diseases [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…This disease, which can predominantly affect the right ventricle (arrhythmogenic right ventricular cardiomyopathy or ARVC), the left ventricle (arrhythmogenic left ventricular cardiomyopathy (ALVC), or arrhythmogenic dilated cardiomyopathy (DCM)), or both (biventricular ACM) is generated by a large spectrum of genes including the lamin A/C gene (LMNA) [1]. Many ACM genes, such as LMNA [3], induce important alterations of the signal transduction and the intercellular communication mechanism in cardiac cells [4][5][6]. In 2015, Lanzicher et al investigated the biomechanical impact of LMNA missense mutations in neonatal rat ventricular myocytes (NRVM), and found damages on the actin cytoskeleton, suggesting loss of actin filament anchorage by dysfunction of the Int.…”
Section: Introductionmentioning
confidence: 99%
“…Sci. 2021, 22, x FOR PEER REVIEW 2 of 23 tion mechanism in cardiac cells [4][5][6]. In 2015, Lanzicher et al investigated the biomechanical impact of LMNA missense mutations in neonatal rat ventricular myocytes (NRVM), and found damages on the actin cytoskeleton, suggesting loss of actin filament anchorage by dysfunction of the laminar proteins at the nuclear membrane as the initiating alteration [7,8].…”
Section: Introductionmentioning
confidence: 99%